B cell targeted therapies in inflammatory autoimmune disease of the central nervous system - Furman, Moritz J.; Meuth, Sven G.; Albrecht, Philipp; Dietrich, Michael; Blum, Heike; Mares, Jan; Milo, Ron; Hartung, Hans-Peter (Frontiers in Immunology, 2023)
Cumulative evidence along several lines indicates that B cells play an important role in the pathological course of multiple sclerosis (MS), neuromyelitisoptica spectrum disorders (NMOSD) and related CNS diseases. This has prompted extensive research in exploring the utility of targeting B cells to contain disease activity in these disorders. In this review, we first recapitulate the development of B cells from their origin in the bone marrow to their migration to the periphery, including the expression of therapy-relevant surface immunoglobulin isotypes. Not only the ability of B cells to produce cytokines and immunoglobulins seems to be essential in driving neuroinflammation, but also their regulatory functions strongly impact pathobiology. We then critically assess studies of B cell depleting therapies, including CD20 and CD19 targeting monoclonal antibodies, as well as the new class of B cell modulating substances, Bruton´s tyrosinekinase (BTK) inhibitors, in MS, NMOSD and MOGAD.